Clinical and Economic Evaluation of Acupuncture for Opioid-Dependent Patients Receiving Methadone Maintenance Treatment: The Integrative Clinical Trial and Evidence-Based Data - Wen, Hao; Wei, Xiaojing; Ge, Shuqi; Zeng, Jingchun; Luo, Wen; Chen, Rouhao; Dong, Yu; Xiao, Songhua; Lai, Yunfeng; Lu, Liming (Frontiers in Public Health, 2021)
Objective: From the health care and societal perspectives, this study aimed to evaluate the clinical and economic effects of acupuncture as an adjunctive therapy for patients receiving methadone maintenance treatment (MMT). Methods: We conducted a parallel-arm RCT in China in 2019. Patients were included who met the diagnostic criteria and receive MMT for more than 30 days. Patients were randomly assigned to the exposed group (acupuncture plus MMT) or control group (MMT) at a 1:1 ratio. Daily methadone dosage, drug cravings using the VAS score, and insomnia using the Pittsburgh Sleep Quality Index (PSQI) were chosen as the effectiveness indexes, and the quality-adjusted life years (QALYs) was chosen as the utility index. Results: Overall, 123 patients were included. The exposed group was significantly (P < 0.05) better than the control group in the improvement of daily methadone dosage (17.68 vs. 1.07), VAS (38.27 vs. 2.64), and PSQI (2.18 vs. 0.30). The QALY was 0.0784 (95%CI: 0.0761–0.0808) for the exposed group and 0.0762 (95%CI: 0.0738–0.0787) for the control group. The total cost of the exposed group (2869.50 CNY) was higher than the control group (2186.04 CNY). The ICER of daily methadone dosage (41.15), VAS (17.86), and PSQI (313.51) were shown to be economically efficient. While ICUR (310,663.64 CNY/QYLY) was higher than the cost suggested by WHO. Conclusion: Acupuncture as an adjuvant therapy for MMT patients realizes its cost-effectiveness by reducing the dosage of methadone, improving drug cravings, and alleviating insomnia. It helps to improve quality of life, but since its cost exceeds what society is willing to pay, further study is needed.